Biomimetic Hybrid Nanozymes with Self-Supplied H+ and Accelerated O2 Generation for Enhanced Starvation and Photodynamic Therapy against Hypoxic Tumors - Yang, Xue; Yang, Ying; Gao, Fang; Wei, Jia-Jia; Qian, Cheng-Gen; Sun, Min-Jie (Nano letters, 2019)
Nanozymes as artificial enzymes that mimicked natural enzyme-like activities have received great attention in cancer diagnosis and therapy. Biomimetic nanozymes require more consideration regarding complicated tumor microenvironments to mimic biological enzymes, thus achieving superior nanozyme activity in vivo. Here we report a biomimetic hybrid nanozyme (named rMGB) which integrates natural enzyme glucose oxidase (GOx) with nanozyme manganese dioxide (MnO2) by mutual promotion for maximizing the enzymatic activity of MnO2 and GOx. Under hypoxia environment, we observed that MnO2 could react with endogenous H2O2 to produce O2 for enhancing the catalytic efficiency of GOx for starvation therapy. Meanwhile, we confirmed that glucose oxidation generated gluconic acid and further improved the catalytic efficiency of MnO2 subsequently. The biochemical reaction cycle, consisting of MnO2, O2, GOx, and H+, was triggered by the tumor microenvironment and accelerated each other so as to achieve self-supplied H+ and accelerate O2 generation, enhancing the starvation therapy, alleviating tumor hypoxia and accelerating the reactive oxygen species generation in photodynamic therapy. This biomimetic hybrid nanozyme would further facilitate the development of biological nanozymes for cancer treatment.